The application of the finite element method for static behaviour analysis of the asymmetrical one-pylon suspension bridge built-in bending cables of different rigidity - Tatjana Grigorjeva; Ainars Paeglitis (Engineering Structures and Technologies, 2018)
The article presents the results of the numerical analysis of the asymmetrical one-pylon suspension bridge built-in rigid cables. The models for the suspension bridge with the cables of different rigidity are analyzed by comparing vertical displacements, bending moments and strains in the structural members of the bridge. The numerical analysis was performed by examining the bridge under symmetrical and asymmetrical loading and different erection methods. The stress-strain state of a single asymmetrical pylon with the cables of different rigidity and the rational relationship between cable rigidity and girder stiffness has been established.